Effect of ionic size compensation by Ag+ incorporation in homogeneous Fe-substituted ZnO: studies on structural, mechanical, optical, and magnetic properties. Issue 43 (5th July 2018) - Bajpai, Gaurav; Srivastava, Tulika; Patra, N.; Moirangthem, Igamcha; Jha, S. N.; Bhattacharyya, D.; Riyajuddin, Sk; Ghosh, Kaushik; Basaula, Dharma R.; Khan, Mahmud; Liu, Shun-Wei; Biring, Sajal; et al.
Abstract : Substituting an ion of different size from that of the host element introduces lattice strain and defects. Abstract : Substituting an ion of different size from that of the host element introduces lattice strain and defects. However, this mismatch may be significantly reduced by substituting an additional ion with a compensating size relative to the dopant. Such a double substitution might offer better solubility irrespective of the local distortions as well as the formation of defects in the valence states. Fe-substituted ZnO has been widely reported with conflicting results primarily arising from lack of chemical and structural homogeneity originating from preparation techniques, compositional fluctuations, and equivocal comprehension of actual solubility limits of the dopants. In this study, Ag ion has been incorporated in Fe-substituted ZnO to compensate the ionic size of Zn1− x [Fe0.8 Ag0.2 ] x O (0 ≤ x ≤ 0.03125) by determining the solubility limit of the homogeneous material and their corresponding structural, mechanical, optical and magnetic properties have been investigated thoroughly. Co-substitution rearranges the lattice and leads to better crystal structures with tunable properties related to the amount of substitution.